1999
DOI: 10.1093/hmg/8.4.673
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Proteasome Involvement in Polyglutamine Disease: Localization to Nuclear Inclusions in SCA3/MJD and Suppression of Polyglutamine Aggregation in vitro

Abstract: Spinocerebellar ataxia type 3, also known as Machado-Joseph disease (SCA3/MJD), is one of at least eight inherited neurodegenerative diseases caused by expansion of a polyglutamine tract in the disease protein. Here we present two lines of evidence implicating the ubiquitin-proteasome pathway in SCA3/MJD pathogenesis. First, studies of both human disease tissue and in vitro models showed redistribution of the 26S proteasome complex into polyglutamine aggregates. In neurons from SCA3/MJD brain, the proteasome l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
251
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(273 citation statements)
references
References 43 publications
22
251
0
Order By: Relevance
“…First, we examined the role of the ubiquitin/proteasome pathway. Aggregates of several polyQ disease proteins in human neurons are ubiquitinated and contain proteasome components (26)(27)(28)40). We used three different mutant yeast strains that affect the ubiquitin/proteasome pathway at different steps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we examined the role of the ubiquitin/proteasome pathway. Aggregates of several polyQ disease proteins in human neurons are ubiquitinated and contain proteasome components (26)(27)(28)40). We used three different mutant yeast strains that affect the ubiquitin/proteasome pathway at different steps.…”
Section: Discussionmentioning
confidence: 99%
“…Because aggregates of Ht (25) and other glutamine-repeat proteins associated with disease (26)(27)(28) are ubiquitinated in mammalian cells and are associated with components of the proteasome, it has been suggested that the ubiquitin/proteasome pathway might be involved in aggregate formation. We were unable to detect ubiquitinated Ht protein in yeast cells (data not shown).…”
Section: Mutant Ht Forms Cytoplasmic Aggregates In Yeastmentioning
confidence: 99%
“…Methods for cell culture, transfection, and IF have been described (3,5,(27)(28). In cotransfections, constructs encoding polyQ proteins or control vector were used at a molar ratio of 1:1 with pEGFP-CBP construct.…”
Section: Methodsmentioning
confidence: 99%
“…The formation of nuclear inclusions depends on the length of poly-Q repeats and on as yet unidentified factors in the host cells. Studies in cell culture systems and in transgenic mice show that the nuclear inclusions recruit molecular chaperones, ubiquitin, and proteasomal subunits (Cummings et al, 1998;Chai et al, 1999b;Kim et al, 2002). The association of the degradative machineries suggests that nuclear inclusions may be involved in the proteolytic clearing of poly-Q aggregated substrates.…”
Section: Introductionmentioning
confidence: 99%